Evaluation of nutritional status in pediatric intensive care unit patients: the results of a multicenter, prospective study in Turkey - Misirlioglu, Merve; Yildizdas, Dincer; Ekinci, Faruk; Ozgur Horoz, Ozden; Tumgor, Gokhan; Yontem, Ahmet; Talay, Mehmet Nur; Kangin, Murat; Tufan, Erennur; Kesici, Selman; Yener, Nazik; Kinik Kaya, Hatice Elif; et al. (Frontiers in Pediatrics, 2023)
Introduction:Malnutrition is defined as a pathological condition arising from deficient or imbalanced intake of nutritional elements.Factors such as increasing metabolic demands during the disease course in the hospitalized patients and inadequate calorie intake increase the risk of malnutrition.The aim of the present study is to evaluate nutritional status of patients admitted to pediatric intensive care units(PICU) in Turkey, examine the effect of nutrition on the treatment process and draw attention to the need for regulating nutritional support of patients while continuing existing therapies. Material and Method:In this prospective multicenter study, the data was collected over a period of one month from PICUs participating in the PICU Nutrition Study Group in Turkey. Anthropometric data of the patients, calorie intake, 90-day mortality, need for mechanical ventilation, length of hospital stay and length of stay in PICU were recorded and the relationship between these parameters was examined. Results:Of the 614 patients included in the study, malnutrition was detected in 45.4 % of the patients.Enteral feeding was initiated in 40.6%(n=249) of the patients at day one upon admission to the PICU. In the first 48 hours, 86.82 %(n=533) of the patients achieved the target calorie intake, and 81.65%(n=307) of the 376 patients remaining in the intensive care unit achieved the target calorie intake at the end of one week.The risk of mortality decreased with increasing upper mid-arm circumference and triceps skin fold thickness Z-score (OR=0.871/0.894; p=0.027/0.024).The risk of mortality was 2.723 times higher in patients who did not achieve the target calorie intake at first 48 hours (p=0.006) and the risk was 3.829 times higher in patients who did not achieve the target calorie intake at the end of one week (p=0.001).The risk of mortality decreased with increasing triceps skin fold thickness Z-score (OR=0.894; p=0.024). Conclusion:Timely and appropriate nutritional support in critically ill patients favorably affects the clinical course.The results of the present study suggest that mortality rate is higher in patients who fail to achieve the target calorie intake at first 48 hours and day seven of admission to PICU.The risk of mortality decreases with increasing triceps skin fold thickness Z-score.